Comparison of financial leverage ratio before and after the use of off-balance sheet financing in firms listed in the Tehran Stock Exchange - Mehdi Mardani; Reza Fallah (Dutch Journal of Finance and Management, 2018)
The aim of this study was to compare the proportion of financial leverage in companies before and after the use of off-balance sheet financing in firms listed in the Tehran Stock Exchange. The research method was causal-comparative descriptive. The population was all the accepted companies in Tehran Stock Exchange (cars and car fragments, petrochemicals, petroleum products, cement, pharmaceutical, home and sugar appliances) between years of 2010 and 2014 that 87 companies were selected at random. Data were analyzed using independent t-test. Results showed that the average financial leverage for companies which have used off-balance sheet financing was equal to 0.6398 and the average financial leverage for companies that did not use off-balance sheet financing has been equal to 0.5612. Therefore, there was no significant difference between averages of the two samples. Other results showed that the average of return on investment (ROI) ratio in companies that used off-balance sheet financing had no significant statistical reference with an average of return on investment (ROI) ratio in companies that did not use off-balance sheet financing. As well, the average of return on owner's equity (ROE) ratio in companies that have used off-balance sheet financing had no significant statistical difference with the average of return on owner's equity (ROE) ratio in companies that have not used off-balance sheet financing.
Keywords: 650; financial leverage; stock exchange; board of directors